Buku Panduan Akademik Sarjana Muda Sesi Akademik 2021/2022 Fakulti Sains Dan Teknologi Pertahanan (Fakulti Sains Dan Teknologi Pertahanan, Universiti Pertahanan Nasional Malaysia, 2021)
The Academic Guidebook for Bachelor's Degree Programme is prepared to assist newly-enrolled UPNM students of Faculty of Science & Defense Technology to understand the processes and procedures that are related to their studies in UPNM. This guidebook provides the basic information on the academic system, programme structures, list of courses offered, references, and other related information.